Konversi Limbah Sarung Tangan Lateks Laboratorium Menjadi Bahan Bakar Cair dan Pemurniannya - W Wangsa; P Prastyo; Dibyo Sumbogo (UPT Laboratorium Terpadu, Universitas Diponegoro, 2020)
Pyrolysis of latex gloves waste has been carried out without catalyst at 200°C for 2 h, producing 15.9% liquid, 45.35% gas, and 38.75% residue from 2000 g of waste, where the liquid product contained wax. The liquid product composed of 94.3% hydrocarbon and 5.71% chlorine compound. This research was focused on the removal of wax and chlorine compound in the purpose of increasing the calorimetric value of the product. Filtration using activated zeolite and distillation at 90ᵒC were choosen to purify the liquid product. The lowest content of wax and chlorine was achieved using filtration techniques. The decrement of wax and chlorine compound in the liquid product increased its physicochemical properties, where the highest calorimetric value was achieved through filtration using activated zeolite, with the calorimetric value of 10715 cal/g.